2015
DOI: 10.1007/s10508-015-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pornography Use Among Couples: Associations with Satisfaction, Stability, and Relationship Processes

Abstract: The present study utilized a sample of 1755 adult couples in heterosexual romantic relationships to examine how different patterns of pornography use between romantic partners may be associated with relationship outcomes. While pornography use has been generally associated with some negative and some positive couple outcomes, no study has yet explored how differences between partners may uniquely be associated with relationship well-being. Results suggested that greater discrepancies between partners in pornog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 41 publications
4
57
2
4
Order By: Relevance
“…In contrast, pornography use has also been found to be associated with more sexual satisfaction among partnered women (Poulsen, Busby, & Galovan, 2013) and greater sexual knowledge, sexual openness, and sexual excitement (Campbell & Kohut, 2017; Daneback, Traeen, & Mansson, 2009; Weinberg, Williams, Kleiner, & Irizarry, 2010). However, when patterns of pornography use among couples differ dramatically between partners, pornography use is associated with lower relationship satisfaction and stability (Willoughby, Carroll, Busby, & Brown, 2016). This finding suggests that the imbalance of use between partners is important.…”
Section: Pornography Use Among Couplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, pornography use has also been found to be associated with more sexual satisfaction among partnered women (Poulsen, Busby, & Galovan, 2013) and greater sexual knowledge, sexual openness, and sexual excitement (Campbell & Kohut, 2017; Daneback, Traeen, & Mansson, 2009; Weinberg, Williams, Kleiner, & Irizarry, 2010). However, when patterns of pornography use among couples differ dramatically between partners, pornography use is associated with lower relationship satisfaction and stability (Willoughby, Carroll, Busby, & Brown, 2016). This finding suggests that the imbalance of use between partners is important.…”
Section: Pornography Use Among Couplesmentioning
confidence: 99%
“…One dyadic study looked at pornography use and perceived sexual quality (Poulsen et al, 2013) and found that male pornography use was negatively associated with both male and female partners’ perceived sexual quality, whereas female pornography use was only associated positively with her own perceived sexual quality. Another dyadic study looked at discrepancies in pornography use and found that large differences in pornography use between male and female partners was associated with more relational aggression among male partners, less sexual desire among female partners, and less positive communication patterns among both partners (Willoughby et al, 2016). Further, other work on pornography use among couples has looked at their intention to use pornography as a means to enhance their sex life (Daneback, Traeen, & Mansson, 2009).…”
Section: A Dyadic Approach To Pornography Use Among Couplesmentioning
confidence: 99%
“…Willoughby et al [12] have argued that the association between pornography use and couple dissatisfaction can be explained by men's aggressiveness, women's lower sex drives, and poor within-couple communication. Muusses et al [48] have stated that men's pornography use is associated with low couple satisfaction and sexual satisfaction, which supports findings by Landripet and Štulhofer [50].…”
Section: Pornography and Infidelitymentioning
confidence: 99%
“…Recent findings suggest that increased SEM consumption may be associated with reduced sexual satisfaction (Yucel & Gassanov, 2010), more negative relationship communication (Maddox, Rhoades, & Markman, 2011), decreased relationship stability (Willoughby, Carroll, Busby, & Brown, 2015) and a higher likelihood of being divorced (Doran & Price, 2014). Studies specifically exploring men's SEM use thus have often focused on problematic or compulsive patterns of use (e.g.…”
Section: Introductionmentioning
confidence: 99%